A Critical Review on the Book Relationship between Religion and Technology and Its "Islamic Technology" Project - Mahmoud Mokhtari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article reviews the book The Relationship between Religion and Technology. The main effort of the book, as the author himself states, is to study the interaction of technology and religion in the context of the Islamic worldview, as well as to present a theory for achieving Islamic technology. The present article first examines the main concern of the book and its place among other publications of the author. Then the research methodology of the book author will be assessed. Finally, a detailed evaluation of the author's project on Islamic technology will be presented. The claim of this article is that the book does not succeed in achieving a coherent theory about Islamic technology, and this effort needs to be modified and completed. In fact, the author's view focuses on the intentions of the designers and users of technological artifacts, not on the structure and physical properties of the artifacts, and thus the concept of "religious technology" is reduced to what the author calls "non-religious technology" (as opposed to anti-religious).